Young teens more likely to develop SUD than young adults after first cannabis use. Issue 6 (6th May 2021) - Knopf, Alison
Abstract : Adolescents aged 12–17 who use cannabis are twice as likely as young adults aged 18–25 to develop a substance use disorder (SUD) within the first year after that use, according to a recent study from the federal government. In addition, these young teens who use any substance — except for alcohol or nicotine — are more likely than young adults to develop a SUD within the year after the first use of cannabis.